S125 Potential interactions of CRACM ion channels with the calcium activated potassium channel KCa3.1 in human lung mast cells. (2nd December 2011) - Ashmole, I; Patel, M; Duffy, S M; Leyland, M; Bradding, P
Abstract : Introduction and Objectives: The influx of extracellular Ca 2+ is essential for the IgE-dependent release of both preformed mediators and newly-generated autacoids and cytokines from human lung mast cells (HLMC). Members of the recently discovered CRACM (also known as Orai) ion channel family may be responsible for this influx. These channels carry Ca 2+ selective currents (ICRAC ) that are activated when endoplasmic reticulum Ca 2+ stores are emptied. The major K + selective conductance in HLMC is generated by the Ca 2+ -activated K + channel KCa 3.1. There appears to be a close functional relationship between CRACM and KCa 3.1 channels. KCa 3.1 channels activated by the influx of extracellular Ca 2+ act to hyperpolarise the cell membrane, thus maintaining the driving force on CRACM channels. Here we investigate whether CRACM and KCa 3.1 channels physically interact. Methods: Vectors were assembled directing the expression of either CRACM1 or CRACM2 channels tagged at their N-terminus with the c-Myc epitope and human KCa 3.1 tagged at its C-terminus with the FLAG epitope. HEK293 cells were transiently transfected to express either a single epitope tagged channel or both a CRACM-myc channel and KCa 3.1-FLAG. Cell lysates were prepared and potential interactions between CRACM and KCa 3.1 proteins tested by immunoprecipitation and immunoblotting. Results: Expression of CRACM1-myc, CRACM2-myc and KCa 3.1-FLAG proteins was confirmed by immunoblotting of lysates of HEK293 cells transiently transfected with the appropriate vector(s). Using an anti c-myc antibody to immunoprecipitate CRACM1-myc protein, KCa 3.1-FLAG was found to be co-immunoprecipitated. Co-immunoprecipitation of KCa 3.1-FLAG was observed only when it was co-expressed with CRACM1-myc. Similarly, using an anti-FLAG antibody to immunoprecipitate KCa 3.1-FLAG protein, CRACM1-myc was co-immunoprecipitated. Again co-immunoprecipitation was dependent on both the CRACM1-myc and KCa 3.1-FLAG proteins being expressed together. In contrast, under identical reaction conditions, no co-immunoprecipitation of KCa 3.1-FLAG was observed when co-expressed with CRACM2-myc. Conclusions: The co-immunoprecipitation of KCa 3.1-FLAG with CRACM1-myc and vice versa provides evidence that these channels do physically interact. Such an interaction in HLMC would make both channels a potential therapeutic target in the treatment of asthma and would allow KCa 3.1 to be added to the growing list of CRACM1 protein binding partners.